Internalization of Islam Faith and Akhlaq al-Karimah in Aqidah Akhlak Subject Learning to Prevent Verbal Bullying at SMK Latifiyah Glagahwero Kalisat, Jember - Amalia, Wahyu; Hasibullah, Muhamad Umar (JOIES (Journal of Islamic Education Studies), 2026)
Verbal bullying remains a common problem in educational environments, including Islamic-based schools. This study aims to analyze forms of verbal bullying and the internalization of aqidah and akhlak values as preventive efforts at SMK Latifiyah Glagahwero Kalisat. This research used a qualitative descriptive approach with data collected through interviews, observations, and documentation involving teachers, school staff, and students. The results show that verbal bullying occurs in the form of mocking, harsh words, and degrading nicknames. The internalization of faith in God and Akhlaq al-karimah values, such as guarding one's speech, empathy, tolerance, and mutual respect, is carried out through Aqidah Akhlak learning, teacher as role model, religious habituation, and character guidance. These efforts contribute to improving students' moral awareness and reducing verbal bullying behavior. Therefore, strengthening faith in Allah and noble moral values, including maintaining proper speech, empathy, tolerance, and mutual respect, plays an important role in creating a safe, religious, and bullying-free school environment.